The relationship between critical thinking ability and vocabulary learning strategy among EFL learners / Noushin Boroushaki - Boroushaki, Noushin (2015)
As an approach to learning, critical thinking is considered important in the field of education due to its possible effects on language learning (Villavicencio, 2011). Thus, the reasons behind the success and failure of EFL learners have provoked researchers to examine different aspects of the process. In language classrooms, the highest priority is assigned to developing the four language skills, with little attention to developing learners’ ability to thinking critically. Notwithstanding the fact that improving learners’ critical thinking ability in the course of learning will enable students to rely on their own decisions and thoughts regarding the strategies and techniques that they would want to employ in learning the language. The present study aims at investigating the relationship between learners’ critical thinking ability and their vocabulary learning strategies, as well as identifying the types of vocabulary learning strategies that learners employ. Furthermore, proficient and less proficient students will be compared based on their critical thinking score and types of strategy use. The subjects were 66 Iranian postgraduate students studying in University Malaya that were selected through a snowball sampling method. The present research is a mixed-method study and the necessary data were collected using Schmitt’s vocabulary learning strategies questionnaire (VLSQ) to identify the types of strategies used by learners; California critical thinking skills test (CCTST) to determine learners’ critical thinking ability; and semi-structured interviews to validate learners’ choices of strategies. To analyze the data, descriptive statistics were used to identify the types of vocabulary learning strategies used by Iranian students. Independent sample t-test was run to investigate the possible significant difference of critical thinking score and vocabulary learning strategy use, between two groups of proficient and less proficient learners. Furthermore, Pearson moment correlation was performed to examine the relationship between iv critical thinking ability and vocabulary learning strategies. The findings revealed that determination strategies were most frequently used followed by metacognitive and memory strategies, while social strategies were found to be the least frequent among the students. Based on the overall mean score of vocabulary learning strategy use, the subjects were reported to be medium strategy users. In addition, the results of the independent sample t-test indicated a significant difference among two groups of learners in their use of cognitive strategies. On the other hand, there was found to be no significant difference between learners’ critical thinking score with respect to their level of language proficiency. The results of the Pearson moment correlation demonstrated that there was no statistically significant relationship between learners’ critical thinking ability and vocabulary learning strategies.